Financial Management Process Optimisation Using BPMN: Land Lot Trading Case at KPRI PERGU Singosari - Merry Hanif Rahma; Anik Kusmintarti; Kurnia Ekasari (STKIP Singkawang, 2025)
This study aims to model and optimise the financial management processes of the land lot trading unit at KPRI PERGU Singosari using Business Process Model and Notation (BPMN). Despite managing multiple business units, the cooperative continues to rely on manual, non-integrated financial systems, particularly in the land lot unit, which requires complex tracking of assets, payments, and reporting. Using the Rapid Application Development (RAD) approach, the study analysed the existing (As-Is) processes, identified performance gaps, and proposed an improved (To-Be) model through BPMN diagrams. The results revealed significant inefficiencies in the current workflows, including redundant data entry, delayed reporting, and a high risk of human error. The proposed BPMN models offered streamlined processes with better integration, transparency, and readiness for future digital system implementation. This research provided a practical framework for cooperatives seeking to enhance financial accountability and aligns with broader goals of digital transformation in cooperative enterprises.